Membrane electrode assembly and method for producing same

By positioning tungsten oxide particles at the electrolyte membrane-anode catalyst interface to decompose hydrogen peroxide and using additional metal elements, the MEA effectively prevents radical-induced deterioration, enhancing durability and conductivity.

JP7599797B2Active Publication Date: 2024-12-16KK TOYOTA CHUO KENKYUSHO +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021073219
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-23
Publication Date
2024-12-16
Estimated Expiration
2041-04-23

AI Technical Summary

Technical Problem

Existing membrane electrode assemblies (MEAs) suffer from radical-induced deterioration of the solid polymer electrolyte, leading to increased resistance, cross-leakage, and reduced lifespan due to thinning of the membrane, with previous solutions like Ce, Ag, and Pt ions diffusing and not effectively addressing the issue.

Method used

Incorporating first fine particles made of compounds like tungsten oxide at the interface between the electrolyte membrane and the anode catalyst layer to decompose hydrogen peroxide into water and oxygen before it forms harmful radicals, combined with optional second metal elements like Ce or Ag to enhance radical scavenging.

Benefits of technology

The solution effectively suppresses electrolyte membrane deterioration by preventing radical formation, maintaining proton conductivity and extending the MEA's durability by selectively placing the first fine particles where degradation is most likely to occur, with additional second metal elements providing synergistic radical scavenging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599797000005
    Figure 0007599797000005
  • Figure 0007599797000006
    Figure 0007599797000006
  • Figure 0007599797000007
    Figure 0007599797000007
Patent Text Reader

Abstract

To provide a membrane electrode assembly capable of suppressing the generation of radicals causing a deterioration in a solid polymer electrolyte.SOLUTION: A membrane electrode assembly includes an electrolyte membrane including a solid polymer electrolyte, an anode catalyst layer bonded to one side of the electrolyte membrane, a cathode catalyst layer bonded to the other side of the electrolyte membrane, and a first fine particle arranged at the interface between the electrolyte membrane and the anode catalyst layer, the first fine particle comprising a first compound having a function to decompose hydrogen peroxide. Such a membrane electrode assembly can be obtained by: adhering a first fine particle comprising a first compound having a function to decompose hydrogen peroxide, to the surface of the electrolyte membrane and / or the surface of the anode catalyst layer on an electrolyte membrane side; forming the anode catalyst layer on the surface of the electrolyte membrane on an anode side such that the side where the first fine particle is adhered faces inside and forming a cathode catalyst layer on the other side of the electrolyte membrane to form a laminate; and heat-treating the laminate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a membrane electrode assembly and a manufacturing method thereof, and more particularly to a membrane electrode assembly containing an additive that has a function of suppressing the generation of radicals that cause deterioration of a solid polymer electrolyte, and a manufacturing method thereof. [Background technology]

[0002] Membrane electrode assemblies (MEAs) are used in the areas where electrochemical reactions occur in soda electrolysis devices, water electrolysis devices, fuel cells, etc. It is said that MEAs are deteriorated when the electrolyte is attacked by radicals generated directly by the direct reaction of oxygen and hydrogen, or by electrochemical reactions, or by radicals generated via hydrogen peroxide. For example, in fuel cells, radical attack is known to increase the resistance of the electrolyte membrane, increase cross leakage, and shorten the lifespan due to thinning. Furthermore, degradation products generated by radical attack may cause catalyst poisoning, which may result in a decrease in electrolytic performance and cell performance.

[0003] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 discloses a membrane electrode assembly that includes an electrolyte membrane and electrodes made of a catalyst layer and a diffusion layer bonded to both sides of the electrolyte membrane, with the peripheral portion of the diffusion layer impregnated with cerium nitrate.

[0004] The same document states: (A) The degradation of the electrolyte membrane due to radicals occurs notably near the center of the MEA but near the periphery, and (B) By adding Ce to the edge of the diffusion layer, it becomes possible to efficiently remove harmful hydrogen peroxide from within the cell without reducing power generation performance. is stated.

[0005] Patent Document 2 describes a fuel cell in which a plurality of unit cells are stacked horizontally (i.e., a fuel cell in which a plurality of unit cells are arranged vertically), (a) The anode-side water-repellent layer and the cathode-side water-repellent layer each contain CeO2 as a radical inhibitor, and (b) The concentration of the radical inhibitor (concentration of dissolved Ce ions) contained in the vertically upper portion of the anode-side water-repellent layer and the cathode-side water-repellent layer is higher than the concentration of the radical inhibitor contained in the vertically lower portion. A fuel cell is disclosed.

[0006] The same document states: (A) In a fuel cell in which multiple single cells are stacked horizontally, even if scavenging control is performed to drain the residual water after the fuel cell is stopped, the amount of residual water in the vertically lower part of the MEA is greater than the amount of residual water in the vertically upper part. (B) When the radical inhibitor is uniformly contained in the water-repellent layer, the amount of radical inhibitor eluted is small in the vertically upper part of the MEA where the residual water amount is small, so that deterioration due to hydroxyl radicals cannot be suppressed. On the other hand, the amount of radical inhibitor eluted is excessive in the vertically lower part of the MEA where the residual water amount is large, so that the proton transfer resistance of the electrolyte membrane increases; and (C) By increasing the concentration of the radical inhibitor contained in the vertically upper portion of the water-repellent layer compared to the concentration of the radical inhibitor contained in the vertically lower portion of the water-repellent layer, it is possible to ensure the amount of radical inhibitor eluted in the vertically upper portion where the amount of residual water is small, while suppressing the amount of radical inhibitor eluted in the vertically lower portion where the amount of residual water is large. is stated.

[0007] Patent Document 3 describes a counterflow type fuel cell in which the flow of fuel gas and the flow of oxidant gas are in opposite directions, as follows: (a) The anode (anode catalyst layer or anode diffusion layer) contains Ag, and (b) The Ag concentration at the fuel gas outlet is higher than the Ag concentration at the fuel gas inlet. A fuel cell is disclosed.

[0008] The same document states: (A) In counterflow type fuel cells, the humidity at the outlet side of the fuel gas is lower than that at the inlet side, so degradation due to radicals is likely to occur; and (B) By making the Ag concentration at the outlet side of the fuel gas higher than that at the inlet side, degradation due to radicals can be suppressed without reducing the power generation performance of the fuel cell. is stated.

[0009] Furthermore, Patent Document 4 discloses a solid polymer electrolyte membrane in which a second layer containing an ion exchange material and platinum-supported carbon is formed on one side of a composite membrane in which an expanded PTFE membrane is impregnated with an ion exchange material. The document describes that dispersing platinum-supported carbon in a high-strength solid polymer electrolyte improves the life of a fuel cell.

[0010] Ce ions and Ag have the effect of scavenging radicals, and therefore, as described in Patent Documents 1 to 3, by adding more Ce ions or Ag to areas that are subject to severe chemical deterioration, the deterioration of the electrolyte membrane can be suppressed to some extent. However, Ce ions and Ag ions tend to diffuse in the in-plane direction and / or in the thickness direction of the electrolyte membrane due to the concentration gradient, and therefore, if Ce ions or Ag ions move from a site where chemical deterioration is severe, the deterioration suppression effect may not be fully exerted.

[0011] Similarly, Pt has a radical scavenging effect. Therefore, as described in Patent Document 4, when Pt-supported carbon is added to a Pt electrolyte membrane, the deterioration of the electrolyte membrane can be suppressed to some extent. However, Pt is also ionized in the electrolyte membrane and may diffuse in the in-plane direction and / or in the film thickness direction due to the concentration gradient. Furthermore, since Pt also has the function of generating hydrogen peroxide, Pt-supported carbon may promote the deterioration of the electrolyte membrane depending on the position where it is added. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2008-098996 A [Patent Document 2] JP 2018-022570 A [Patent Document 3] JP 2019-160604 A [Patent Document 4] JP 2014-139939 A Summary of the Invention [Problem to be solved by the invention]

[0013] An object of the present invention is to provide a membrane electrode assembly capable of suppressing the generation of radicals that cause deterioration of a solid polymer electrolyte. Another problem to be solved by the present invention is to provide a membrane electrode assembly capable of suppressing deterioration of an electrolyte membrane over a long period of time. [Means for solving the problem]

[0014] In order to solve the above problems, the membrane electrode assembly according to the present invention comprises: an electrolyte membrane including a solid polymer electrolyte; an anode catalyst layer bonded to one surface of the electrolyte membrane; a cathode catalyst layer bonded to the other surface of the electrolyte membrane; a first fine particle disposed at the interface between the electrolyte membrane and the anode catalyst layer; Equipped with The first fine particles are made of a first compound having a function of decomposing hydrogen peroxide.

[0015] The method for producing a membrane electrode assembly according to the present invention includes the steps of: a first step of attaching first fine particles made of a first compound having a function of decomposing hydrogen peroxide to a surface of an electrolyte membrane and / or a surface of an anode catalyst layer facing the electrolyte membrane; a second step of forming the anode catalyst layer on the anode side surface of the electrolyte membrane such that the surface to which the first fine particles are attached faces inward, and further forming a cathode catalyst layer on the other side of the electrolyte membrane to form a laminate; a third step of heat-treating the laminate to obtain a membrane electrode assembly according to the present invention; It is equipped with: Effect of the Invention

[0016] Deterioration of the electrolyte membrane is (a) Oxygen that has permeated from the cathode to the anode reacts with hydrogen on the anode catalyst to produce H2O2, (b) H2O2 produced on the anode catalyst diffuses into the electrolyte membrane, where it reacts with Fe, an impurity in the electrolyte membrane, to produce hydroxyl radicals. (c) Hydroxyl radicals decompose electrolytes. This is thought to be caused by the

[0017] Therefore, if the first fine particles having the function of decomposing hydrogen peroxide are present at the interface between the electrolyte membrane and the anode catalyst layer, the H2O2 generated at the anode is decomposed into water and oxygen before it becomes hydroxyl radicals. As a result, the decomposition of the electrolyte membrane is suppressed, and the chemical durability of the electrolyte membrane is improved. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram of a fuel cell equipped with a gas flow path structure that allows fuel gas (hydrogen) and oxidant gas (air) to flow in a predetermined direction. [Diagram 2] 2(A) is an SEM image of a cross section of the membrane electrode assembly obtained in Example 1. FIG. 2(B) is an SEM image of a cross section of the membrane electrode assembly obtained in Comparative Example 2. [Diagram 3] Fig. 3(A) is an SEM image of the electrolyte membrane surface after the anode catalyst layer was peeled off from the membrane electrode assembly obtained in Example 1. Fig. 3(B) is an SEM image of the electrolyte membrane surface after the anode catalyst layer was peeled off from the membrane electrode assembly obtained in Comparative Example 2. [Figure 4] FIG. 1 is a diagram showing application positions of solutions containing various additives and quantitative determination positions of W or Ce. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] An embodiment of the present invention will be described in detail below. [1. Membrane electrode assembly] The membrane electrode assembly (hereinafter also referred to as "MEA") according to the present invention is an electrolyte membrane including a solid polymer electrolyte; an anode catalyst layer bonded to one surface of the electrolyte membrane; a cathode catalyst layer bonded to the other surface of the electrolyte membrane; a first fine particle disposed at the interface between the electrolyte membrane and the anode catalyst layer; It is equipped with:

[0020] [1.1. Electrolyte membrane] The electrolyte membrane contains a solid polymer electrolyte. In the present invention, the type of the solid polymer electrolyte contained in the electrolyte membrane is not particularly limited. The solid polymer electrolyte may be either a fluorine-based electrolyte or a hydrocarbon-based electrolyte. The electrolyte membrane may contain any one of these solid polymer electrolytes, or may contain two or more of them. The type of acid group in the solid polymer electrolyte is not particularly limited. Examples of the acid group include a sulfonic acid group, a carboxylic acid group, a phosphonic acid group, and a sulfonimide group. The solid polymer electrolyte may contain only one of these acid groups, or may contain two or more of them.

[0021] Examples of fluorine-based electrolytes include Nafion (registered trademark), Flemion (registered trademark), Aquivion (registered trademark), and Aciplex (registered trademark). The fluorine-based electrolyte includes not only fully fluorine-based electrolytes that do not contain C—H bonds in the polymer structure, but also partially fluorine-based electrolytes that contain C—H bonds and C—F bonds in the polymer structure.

[0022] Examples of the hydrocarbon electrolyte include: (a) A wholly aromatic hydrocarbon-based electrolyte comprising polyether ether ketone, polysulfone, polyether sulfone, polyimide, polyphenylene, polyamide, polyamide imide, or a derivative thereof, into which an acid group such as a sulfonic acid group has been introduced; (b) partially aromatic hydrocarbon electrolytes having an aromatic ring in a part of the polymer chain of an aliphatic hydrocarbon electrolyte; etc.

[0023] Furthermore, the electrolyte membrane may be made of only a solid polymer electrolyte (composite electrolyte) containing various additives, or may be a composite of a composite electrolyte and a reinforcing material. In this case, the type of the reinforcing material is not particularly limited. Examples of reinforcing materials include: (a) Porous membranes and nonwoven fabrics of fluororesins such as polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), and ethylenetetrafluoroethylene copolymer (ETFE); (b) Porous membranes and nonwoven fabrics of hydrocarbon resins such as polyethylene (PE) and polypropylene (PP), etc.

[0024] [1.2. Anode catalyst layer] An anode catalyst layer is bonded to one side of the electrolyte membrane. The anode catalyst layer includes an electrode catalyst (anode catalyst) active in hydrogen oxidation reaction and a catalyst layer ionomer. The anode catalyst may be composed of only catalyst particles (A) active in hydrogen oxidation reaction, or the catalyst particles (A) may be supported on the surface of a carrier. In the present invention, the materials of the catalyst layer ionomer, the catalyst particles (A), and the carrier are not particularly limited, and the most suitable materials can be selected depending on the purpose.

[0025] The catalyst layer ionomer on the anode side may be made of the same material as the solid polymer electrolyte constituting the electrolyte membrane, or may be made of a different material. The catalyst particles (A) include, for example, precious metals, alloys containing two or more precious metals, and alloys of one or more precious metals and one or more base metals. Examples of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.

[0026] [1.3. Cathode catalyst layer] A cathode catalyst layer is bonded to the other surface of the electrolyte membrane. The cathode catalyst layer includes an electrode catalyst (cathode catalyst) active in the oxygen reduction reaction and a catalyst layer ionomer. The cathode catalyst may be composed only of catalyst particles (B) active in the oxygen reduction reaction, or the catalyst particles (B) may be supported on the surface of a carrier. In the present invention, the materials of the catalyst layer ionomer, the catalyst particles (B), and the carrier are not particularly limited, and the most suitable materials can be selected depending on the purpose.

[0027] The catalyst layer ionomer on the cathode side may be made of the same material as the solid polymer electrolyte constituting the electrolyte membrane, or may be made of a different material. Examples of the catalyst particles (B) include precious metals, alloys containing two or more precious metals, and alloys containing one or more precious metals and one or more base metals. Examples of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.

[0028] [1.4. First fine particle] [1.4.1. Materials] The "first fine particles" refer to fine particles made of a first compound (inorganic compound) having the function of decomposing hydrogen peroxide. The type of the first compound is not particularly limited as long as it has the function of decomposing hydrogen peroxide. Examples of the first compound include a tungsten compound and a molybdenum compound. Among these, the first compound is preferably a tungsten compound, which has a higher hydrogen peroxide decomposition ability than other materials and is therefore suitable as a material for the first fine particles.

[0029] Examples of tungsten compounds include: (a) Tungsten oxide (+IV, +V, +VI), (b) Tungstate etc. The first fine particles may be made of any one of these, or may be a mixture containing two or more of them.

[0030] Tungsten oxide may be anhydrous or hydrated. Tungsten oxide is particularly preferably WO3·(1 / 3)H2O or WO3·2H2O. WO3 1 / 3 hydrate or dihydrate has a significantly higher hydrogen peroxide decomposition ability than other tungsten oxides, and is therefore particularly suitable as a material for the first microparticles. Examples of tungstates include Al2(WO4)3, BaWO4, FeWO4, Ni2WO4, Cu2WO4, ZnWO4, and Ce2(WO4)3.

[0031] [1.4.2. Position of the first particle] [A. Position in film thickness direction] The first fine particles are disposed at the interface between the electrolyte membrane and the anode catalyst layer, which is different from conventional techniques. Hydrogen peroxide is generated when oxygen that has permeated from the cathode to the anode reacts with hydrogen on the anode catalyst. In order for hydrogen peroxide generated on the anode catalyst to be decomposed into water and oxygen before it becomes radicals, the closer the position of the first fine particles is to the anode side, the better. In order to suppress deterioration due to radicals, the first fine particles are preferably disposed at the interface between the electrolyte membrane and the anode-side catalyst layer.

[0032] [B. In-plane position] The first fine particles may be present uniformly over the entire interface between the electrolyte membrane and the anode catalyst layer, or may be unevenly distributed in the in-plane direction (that is, present only in a part of the interface).

[0033] A gas diffusion layer is usually placed on the outside of the MEA, and a separator (also called a "current collector") equipped with gas flow channels is further placed on the outside of the gas diffusion layer. There are various structures for the gas flow path (i.e., the method of flowing the fuel gas and oxidant gas). Meanwhile, the structure of the gas flow path not only determines the direction of the gas flow, but also affects the temperature distribution, humidity distribution, etc. in the cell. Furthermore, when the temperature distribution, humidity distribution, etc. in the cell change, the deterioration rate of the electrolyte membrane also changes depending on the position. Therefore, it is preferable to unevenly distribute the first fine particles in positions where deterioration of the electrolyte membrane is likely to occur, rather than dispersing them uniformly in the in-plane direction.

[0034] A schematic diagram of a fuel cell equipped with a gas flow path structure that allows the fuel gas (hydrogen) and oxidant gas (air) to flow in a predetermined direction is shown in Figure 1. The numbers shown in Figure 1 represent the regions of the divided MEA. In Fig. 1, fuel gas is introduced from the end of region 1 in the x-axis direction. Hydrogen gas introduced into region 1 flows through regions 1, 4, 7, 8, 5, 2, 3, 6, and 9 in this order, and is discharged from the end of region 9 in the x-axis direction. On the other hand, oxidant gas is introduced from the ends of regions 3, 6, and 9 in the y-axis direction. The oxidant gas introduced into regions 3, 6, and 9 flows in the y-axis direction, and is discharged from the ends of regions 1, 4, and 7 in the y-axis direction.

[0035] In the example shown in Fig. 1, the humidity in the cell is lower in the regions 1, 3, 6, and 9 than in other regions, and the electrolyte membrane is more likely to deteriorate in these regions. Therefore, it is preferable to add the first fine particles to these regions in a larger amount than to the other regions. Specifically, it is preferable to place 50 to 100% of the total amount of the first fine particles present at the interface in the region where deterioration is likely to occur.

[0036] [1.4.3. Average content of first fine particles] The "average content" refers to the ratio of the mass of the first fine particles to the total mass of the solid polymer electrolyte and the first fine particles contained in the electrolyte membrane in the region where the first fine particles are disposed, when the first fine particles are disposed at the interface between the electrolyte membrane and the anode catalyst layer.

[0037] The average content of the first fine particles affects the durability of the membrane electrode assembly. The higher the average content of the first fine particles, the more the durability of the membrane electrode assembly improves. To obtain such an effect, the average content of the first fine particles is preferably 0.01 mass% or more. The average content is more preferably 0.05 mass% or more, and even more preferably 0.1 mass% or more.

[0038] When the first fine particles are dispersed in the electrolyte membrane, if the average content of the first fine particles is excessive, the electrolyte membrane may crack. However, when the first fine particles are disposed at the interface, the electrolyte membrane will not crack even if the average content is excessive. However, if the average content of the first fine particles is excessive, the proton conductivity of the electrolyte membrane may decrease. Therefore, the average content of the first fine particles is preferably 20.0 mass% or less. The average content is more preferably 10.0 mass% or less, and even more preferably 5.0 mass% or less.

[0039] [1.4.4. Average particle size of first fine particles] The term "average particle size of the first fine particles" refers to the average value of the maximum dimension of 20 or more first fine particles randomly selected under microscope observation.

[0040] The average particle size of the first fine particles is not particularly limited, and an optimal average particle size can be selected depending on the purpose. In general, if the average particle size of the first fine particles is too large, the first fine particles may break through the membrane, causing a short circuit or a leak. Therefore, the average particle size of the first fine particles is preferably 1 / 10 or less of the membrane thickness of the electrolyte membrane. The average particle size is more preferably 1 / 100 or less, and even more preferably 1 / 5000 or less of the membrane thickness of the electrolyte membrane. On the other hand, if the average particle size of the first fine particles is too small, the first fine particles tend to dissolve. Therefore, the average particle size of the first fine particles is preferably 0.1 nm or more. The average particle size is more preferably 1.0 nm or more, and even more preferably 2.0 nm or more.

[0041] [1.5. Ions of second metal element and / or second fine particles] [1.5.1. Materials] The "second metal element" refers to a metal element having a function of scavenging radicals. The term "second compound" refers to a compound containing a second metallic element. The "second fine particles" refer to fine particles made of a second compound.

[0042] Compounds and ions containing certain metal elements mainly have the effect of scavenging radicals, and therefore, by adding an appropriate amount of fine particles of compounds containing such metal elements and / or ions of such metal elements to the electrolyte membrane, deterioration of the electrolyte membrane can be further suppressed.

[0043] Examples of the second metal element include Ce, Ag, Cs, Sn, Mn, Ti, Co, Ni, Zn, Zr, Ru, Rh, Pd, Pt, Pr, etc. The electrolyte membrane may contain any one of these elements, or may contain two or more of them. Among these, the second metal element is preferably at least one element selected from the group consisting of Ce, Ag, Cs, Sn, and Mn. The second metal element is particularly preferably Ce, because these elements have a large effect of suppressing the generation of radicals or scavenging radicals.

[0044] The second compound may be a water-soluble compound or a poorly soluble compound. When a water-soluble second compound is used, the second compound dissociates in the electrolyte membrane, and some of the protons of the acid groups of the solid polymer electrolyte are replaced with ions of the second metal element. On the other hand, when a poorly soluble second compound is used, the second compound is dispersed in the electrolyte membrane. The second compound may be, for example, a nitrate, sulfate, carbonate, formate, acetate, citrate, perchlorate, phosphate, chloride, fluoride, hydroxide, or acetylacetonate compound.

[0045] [1.5.2. Content] When the electrolyte membrane contains ions of the second metal element and / or second fine particles, it is preferable that the electrolyte membrane satisfies the following formula (1). 0.0005≦M / A≦0.15 …(1) however, M / A is the ratio of the number of moles (M) of the second metal element to the number of moles (A) of acid groups contained in the solid polymer electrolyte.

[0046] Even when only the first fine particles are arranged at the interface between the electrolyte membrane / anode catalyst layer, the deterioration of the electrolyte membrane can be effectively suppressed. However, when the second compound and / or ions of the second metal element are further added to the electrolyte membrane in addition to the first fine particles, the deterioration of the electrolyte membrane is further suppressed due to the synergistic effect of these. To obtain such an effect, the M / A ratio is preferably 0.0005 or more. The M / A ratio is preferably 0.001 or more, more preferably 0.005 or more.

[0047] On the other hand, if the M / A ratio is too large, the conductivity of the electrolyte membrane may decrease. Therefore, the M / A ratio must be 0.15 or less. The M / A ratio is preferably 0.10 or less, more preferably 0.05 or less, more preferably 0.04 or less, and even more preferably 0.03 or less.

[0048] [1.5.3. Average particle size] When the second fine particles are added to the electrolyte membrane, the average particle size of the second fine particles is not particularly limited, and the most suitable average particle size can be selected according to the purpose. Other points regarding the average particle size of the second fine particles are the same as those of the first fine particles, so the explanation is omitted.

[0049] [1.5.4. Location of the second metallic element ion or second particle] The position where the ions of the second metal element and the second fine particles are added is not particularly limited. Since radicals are not necessarily generated on the anode side, the ions of the second metal element and the second fine particles may be added on the cathode side.

[0050] [2. Manufacturing method of membrane electrode assembly] The method for producing a membrane electrode assembly according to the present invention includes the steps of: a first step of attaching first fine particles made of a first compound having a function of decomposing hydrogen peroxide to a surface of an electrolyte membrane and / or a surface of an anode catalyst layer facing the electrolyte membrane; a second step of forming the anode catalyst layer on the anode side surface of the electrolyte membrane such that the surface to which the first fine particles are attached faces inward, and further forming a cathode catalyst layer on the other side of the electrolyte membrane to form a laminate; a third step of heat-treating the laminate to obtain a membrane electrode assembly according to the present invention; It is equipped with:

[0051] [2.1. 1st step] First, first fine particles made of a first compound having a function of decomposing hydrogen peroxide are attached to the surface of the electrolyte membrane and / or the surface of the anode catalyst layer facing the electrolyte membrane (first step).

[0052] The method for adhering the first fine particles is not particularly limited, and an optimal method can be selected depending on the purpose. Examples of the method for adhering the first fine particles include (a) A method of spraying a dispersion liquid having first fine particles dispersed therein onto a surface of an electrolyte membrane or a surface of an anode catalyst layer, and drying the dispersion liquid; (b) A method of applying first fine particles onto a surface of an electrolyte membrane or a surface of an anode catalyst layer by using a dry coating method such as electrostatic screen printing; etc.

[0053] The first fine particles may be attached only to either the surface of the electrolyte membrane or the surface of the anode catalyst layer, or may be attached to both. The first fine particles may be attached to the entire surface of the electrolyte membrane and / or the entire surface of the anode catalyst layer, or may be attached only to a part of the surface.

[0054] Examples of a method for adding ions of the second metal element or second fine particles to the electrolyte membrane include: (a) A method of adding second fine particles or a solvent-soluble compound containing a second metal element to a casting solution for producing an electrolyte membrane; (b) A method in which after preparing an electrolyte membrane, a solution containing ions of a second metal element is applied to the surface of the electrolyte membrane, and the ions of the second metal element are diffused into the electrolyte membrane; (c) a method in which after preparing an electrolyte membrane, a solution containing ions of a second metal element is applied to a surface of the electrolyte membrane, the ions of the second metal element are diffused into the electrolyte membrane, and a second compound is precipitated in the electrolyte membrane; etc.

[0055] [2.2. 2nd process] Next, the anode catalyst layer is formed on the anode side surface of the electrolyte membrane so that the surface to which the first fine particles are attached faces inward, and further, a cathode catalyst layer is formed on the other side of the electrolyte membrane to form a laminate (second step).

[0056] The method for forming the catalyst layer is not particularly limited. Examples of the method for forming the catalyst layer include (a) A method of forming a catalyst layer on a substrate surface and transferring the catalyst layer to a surface of an electrolyte membrane; (b) A method of applying a paste for forming a catalyst layer on the surface of an electrolyte membrane and drying the paste; etc. When the catalyst layer is formed by the transfer method, the first fine particles may be attached to the surface of the catalyst layer, or may be attached to the surface of the electrolyte membrane.

[0057] [2.3. Third step] Next, the laminate is heat-treated (third step), thereby obtaining a membrane / electrode assembly according to the present invention. The heat treatment conditions are not particularly limited, and the optimum conditions can be selected depending on the purpose. The heat treatment is usually performed at 1 kgf / cm 2 (9.8×10 -2 MPa)~100kgf / cm 2 The curing process is carried out by heating at 25°C to 200°C for 1 to 20 minutes while applying a pressure of 100 MPa (9.8 MPa).

[0058] [3. Effect] Deterioration of the electrolyte membrane is (a) Oxygen that has permeated from the cathode to the anode reacts with hydrogen on the anode catalyst to produce H2O2, (b) H2O2 produced on the anode catalyst diffuses into the electrolyte membrane, where it reacts with Fe, an impurity in the electrolyte membrane, to produce hydroxyl radicals. (c) Hydroxyl radicals decompose electrolytes. This is thought to be caused by the

[0059] Therefore, if the first fine particles having the function of decomposing hydrogen peroxide are present at the interface between the electrolyte membrane and the anode catalyst layer, the H2O2 generated at the anode is decomposed into water and oxygen before it becomes hydroxyl radicals. As a result, the decomposition of the electrolyte membrane is suppressed, and the chemical durability of the electrolyte membrane is improved. In particular, tungsten oxide and tungstate do not dissolve in the fuel cell environment (acidity, potential) and can exist in the form of fine particles at the interface between the electrolyte membrane and the anode catalyst layer. Therefore, dissolved ions do not exchange with sulfonic acid groups in the electrolyte, and high proton conductivity can be maintained, so that the cell performance does not decrease. Furthermore, among tungsten oxides, WO3·(1 / 3)H2O and WO3·2H2O have a significantly higher hydrogen peroxide decomposition ability than other materials, and therefore, when placed at the electrolyte membrane / anode catalyst layer interface, the chemical durability of the electrolyte membrane is improved.

[0060] In addition, the first fine particles, which are stable under the fuel cell operating environment, do not move inside the membrane electrode assembly, and therefore, by selectively disposing the first fine particles in areas of the electrolyte membrane where deterioration is severe using the method according to the present invention, deterioration of the electrolyte membrane can be efficiently suppressed, and the effect of suppressing deterioration can be maintained for a long period of time.

[0061] Furthermore, by further adding second fine particles and / or ions of a second metal element to the electrolyte membrane in addition to disposing the first fine particles at the electrolyte membrane / anode catalyst layer interface, high durability can be obtained even if the amounts of these added are relatively small. (a) The first fine particles have the effect of decomposing hydrogen peroxide to render it harmless, and even if the amount added is small, they exhibit a high hydrogen peroxide decomposition effect. (b) The second fine particles and the ions of the second metal element have the effect of scavenging radicals, (c) When the first fine particles are coexisted with the second fine particles and / or ions of the second metal element, the hydrogen peroxide decomposition effect of the first fine particles is improved, and / or (d) Even if radicals are generated from hydrogen peroxide that is not decomposed by the first fine particles, the second fine particles and / or ions of the second metal element effectively eliminate the radicals, It is thought that. EXAMPLES

[0062] (Example 1, Comparative Examples 1-2) [1. Sample preparation] [1.1. Preparation of electrolyte membrane] 1.1.1. Example 1 An electrolyte solution (D2020, Nafion (registered trademark) dispersion, 1000EW, 20 mass%, manufactured by Chemours), 1-propanol, and ultrapure water were mixed so that the electrolyte solution: 1-propanol: water = 10: 7: 3 (mass ratio). Furthermore, the electrolyte was dispersed by irradiating the mixed solution with ultrasonic waves for 10 minutes, and a cast solution was obtained.

[0063] Cast solution: 1.20 g was placed in a φ35 mm flat dish and left in a thermostatic room atmosphere (25°C) for several days to dry out. Next, the dish was annealed at 140°C for 15 minutes. After annealing, the membrane was washed five times with ultrapure water. Furthermore, the membrane was peeled off from the dish and air-dried.

[0064] Next, an ethanol solution in which WO3 was dispersed at a rate of 1 mass% was prepared. The ethanol solution was applied to the surface of the electrolyte membrane using an atomizer spray to obtain a composite electrolyte membrane. The applied area of ​​WO3 was 4 cm2. 2 The amount of WO3 applied was set so that the average content of WO3 in the applied area (the ratio of the mass of WO3 to the total mass of the solid polymer electrolyte and WO3 contained in the applied area) was 20 mass%.

[0065] [1.1.2. Comparative Examples 1-2] An electrolyte solution (D2020, Nafion (registered trademark) dispersion, 1000EW, 20 mass%, manufactured by Chemours), 1-propanol, and ultrapure water were mixed to give an electrolyte solution: 1-propanol: water = 10: 7: 3 (mass ratio), and then WO3 was added. The amount of WO3 added was set to an amount such that the average content in the entire membrane (the mass ratio of WO3 to the total mass of the solid polymer electrolyte and WO3 contained in the entire membrane) was 20 mass% (Comparative Example 1) or 3 mass% (Comparative Example 2). Furthermore, the electrolyte was dispersed by irradiating the mixed solution with ultrasonic waves for 10 minutes, and a cast solution was obtained.

[0066] Cast solution: 1.20 g was placed in a φ35 mm flat dish and left in a thermostatic room atmosphere (25°C) for several days to dry out. Next, the dish was annealed at 140°C for 15 minutes. After annealing, the membrane was washed five times with ultrapure water. Furthermore, the membrane was peeled off from the dish and air-dried.

[0067] [1.2. Preparation of MEA] Catalyst layers are thermally transferred onto both sides of the electrolyte membrane (145°C, 5 minutes, 60kgf / cm 2 (5.9 MPa) to prepare an MEA.

[0068] 2. Test Method [2.1. Visual evaluation of cracks] Before preparing the MEA, the electrolyte membrane was visually evaluated for cracks. [2.2. Scanning transmission electron microscope (SEM) observation] A scanning transmission electron microscope (SEM) was used to observe the cross section of the obtained MEA and the surface of the electrolyte membrane after the anode catalyst layer was peeled off from the MEA.

[0069] [3. Results] [3.1. Visual evaluation of cracks] The results are shown in Table 1. Cracks were found in the electrolyte membrane in Comparative Example 1. On the other hand, no cracks were found in the electrolyte membrane in Example 1 and Comparative Example 2.

[0070] [Table 1]

[0071] [3.2. SEM Observation] Fig. 2(A) shows an SEM image of a cross section of the membrane electrode assembly obtained in Example 1. Fig. 2(B) shows an SEM image of a cross section of the membrane electrode assembly obtained in Comparative Example 2. In the case of the MEA produced by the spray method (Example 1), WO3 was present at the interface between the electrolyte membrane and the anode catalyst layer. On the other hand, in the case of the MEA produced by the cast method (Comparative Example 2), WO3 segregated to the anode side in the electrolyte membrane, but no WO3 layer was observed at the interface between the electrolyte membrane and the anode catalyst layer.

[0072] Fig. 3(A) shows an SEM image of the electrolyte membrane surface after the anode catalyst layer was peeled off from the membrane electrode assembly obtained in Example 1. Furthermore, Fig. 3(B) shows an SEM image of the electrolyte membrane surface after the anode catalyst layer was peeled off from the membrane electrode assembly obtained in Comparative Example 2. In the case of Comparative Example 2, most of the surface of the electrolyte membrane after the anode catalyst layer was peeled off was composed of electrolyte, and almost no WO3 was found exposed on the surface of the electrolyte membrane, whereas in the case of Example 1, only WO3 was found on the surface of the electrolyte membrane after the anode catalyst layer was peeled off.

[0073] (Example 2, Comparative Example 3) [1. Sample preparation] 1.1. Example 2 In the same manner as in Example 1, WO powder was applied to the anode side surface of the electrolyte membrane (application area: 4 cm 2 ) An electrolyte membrane was fabricated.

[0074] [1.2. Comparative Example 3] In the same manner as in Example 1, a cast membrane consisting of only the electrolyte was prepared. Next, an aqueous solution was prepared in which cerium nitrate was dispersed at a rate of 1 mass%. The aqueous solution was applied to the surface of the electrolyte membrane using an atomizer spray to obtain a composite electrolyte membrane. The applied area of ​​Ce was 4 cm2. 2 The amount of Ce applied was set to be equivalent to 20% of the amount of sulfonic acid groups in the electrolyte membrane in the applied area.

[0075] 2. Test Method The obtained electrolyte membrane was left for 72 hours under conditions of 80° C. and 80% RH. After that, the amount of W or Ce contained in the electrolyte membrane was quantified, and the values ​​before and after the test were compared. Figure 4 shows the application positions of the solutions containing various additives and the quantitative determination positions of W or Ce. As shown in Figure 4, the various additives were applied to approximately the center of the electrolyte membrane. Furthermore, the quantitative determination of W or Ce was performed at two locations: an area approximately in the center of the additive application area (quantitative determination position 1), and an area where the additive was not applied (quantitative determination position 2).

[0076] [3. Results] The results are shown in Table 2. In the case of Example 2, the amount of W at the quantitative determination position 1 hardly changed before and after the test. Moreover, the amount of W at the quantitative determination position 2 was zero both initially and after the test. On the other hand, in the case of Comparative Example 3, the amount of Ce at quantification position 1 was greatly reduced after the test. Also, at quantification position 2, a small amount of Ce was already detected even in the initial state, and the amount of Ce increased after the test. From the above results, it was found that by selectively adding WO3 to areas where it is desired to suppress deterioration, the effect of suppressing deterioration in those areas can be sustained for a long period of time.

[0077] [Table 2]

[0078] (Examples 4 to 10, Comparative Example 4) [1. Test method] 0.067 mmol of each additive was dispersed in 10 mL of water to prepare a dispersion, and 4.41 mmol of hydrogen peroxide was further added to this dispersion. The additives used were as follows: (a) Aluminum tungstate (Al2(WO4)3) (Example 4) (b) Barium tungstate (BaWO4) (Example 5) (c) Iron tungstate (FeWO4) (Example 6) (d) Nickel tungstate (Ni2WO4) (Example 7) (e) Copper tungstate (Cu2WO4) (Example 8) (f) Zinc tungstate (ZnWO4) (Example 9) (g) WO2 (Example 10) (h) No additives (Comparative Example 4)

[0079] The resulting dispersion was kept at 80° C. for 1 hour, and then the concentration of hydrogen peroxide remaining in the dispersion was measured. Furthermore, the hydrogen peroxide decomposition rate was calculated from the following formula (2). Hydrogen peroxide decomposition rate (%) = (C0-C) x 100 / C0…(2) however, C0 is the concentration of hydrogen peroxide in the original dispersion, C is the concentration of hydrogen peroxide in the dispersion after holding at 80°C for 1 hour.

[0080] [2. Results] Table 3 shows the H2O2 decomposition rate of various additives. It was found that under these experimental conditions, H2O2 did not undergo self-decomposition due to heat (Comparative Example 4). On the other hand, H2O2 decomposed not only when WO2 in Example 10 was used, but also when various tungstates in Examples 4 to 9 were used. From the above, it is expected that chemical degradation can be suppressed by disposing tungstate at the interface between the electrolyte and the anode-side catalyst layer.

[0081] [Table 3]

[0082] (Examples 11 to 12, Comparative Example 5) [1. Sample preparation] 1.1. Example 11 An MEA was produced in the same manner as in Example 1, except that iron sulfate was further added to the casting solution in an amount such that 1% of the sulfonic acid groups in the electrolyte membrane were substituted with Fe ions. [1.2. Comparative Example 5] An MEA was produced in the same manner as in Comparative Example 2, except that iron sulfate was further added to the casting solution in an amount such that 1% of the sulfonic acid groups in the electrolyte membrane were substituted with Fe ions. 1.3. Example 12 An MEA was prepared in the same manner as in Example 1, except that iron sulfate in an amount such that 1% of the sulfonic acid groups in the electrolyte membrane were substituted with Fe ions, and cerium nitrate in an amount such that 4.4% of the sulfonic acid groups in the electrolyte membrane were substituted with Ce ions were further added to the casting solution.

[0083] 2. Test Method Gas diffusion layers were placed on both sides of the obtained MEA, and the MEA was assembled into a fuel cell. The electrode area was 0.64 cm 2 Next, the obtained fuel cell was subjected to an open circuit (OC) durability test for 90 hours under the following conditions. Cell temperature: 95℃ Humidity: 30% RH for both anode and cathode Gas flow rate: 300cc / min (anode: H2, cathode: O2) Back pressure: 133kPa

[0084] The humidified gas discharged from the fuel cell during the test was condensed, and the resulting water was collected every 24 hours. The collected water contained dissolved F ions that had been chemically decomposed from the electrolyte membrane. These were quantified using ion chromatography, and the cumulative amount of F ions up to 90 hours was calculated.

[0085] [3. Results] The results are shown in Table 4. From Table 4, it can be seen that the amount of F elution in Example 11 is smaller than that in Comparative Example 5. This is believed to be because hydrogen peroxide was efficiently decomposed by distributing WO2 unevenly at the electrolyte membrane / anode catalyst layer interface. Furthermore, the amount of F elution in Example 12 was even smaller than that in Example 11, confirming the effect of the combined addition of Ce and W.

[0086] [Table 4]

[0087] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0088] The membrane electrode assembly according to the present invention can be used in various electrochemical devices such as solid polymer fuel cells and solid polymer water electrolysis devices.

Claims

1. an electrolyte membrane including a solid polymer electrolyte; an anode catalyst layer bonded to one surface of the electrolyte membrane; a cathode catalyst layer bonded to the other surface of the electrolyte membrane; First fine particles present at the interface between the electrolyte membrane and the anode catalyst layer; Equipped with The first fine particles are made of a first compound having a function of decomposing hydrogen peroxide. Membrane electrode assembly.

2. 2. The membrane electrode assembly of claim 1, wherein the first compound comprises a tungsten compound.

3. 3. The membrane electrode assembly according to claim 1, wherein the first compound is made of tungsten oxide (+IV, +V, +VI) or a tungstate.

4. 4. The membrane / electrode assembly according to claim 1, wherein an average content of the first fine particles is 0.01 mass % or more and 20.0 mass % or less.

5. 5. The membrane electrode assembly according to claim 1, wherein an average particle diameter of the first fine particles is equal to or smaller than 1 / 10 of a thickness of the electrolyte membrane.

6. (a) ions of a second metal element having a radical scavenging function, which are ion-exchanged with protons of the acid groups of the solid polymer electrolyte, and / or (b) second fine particles made of a second compound containing the second metal element, the second fine particles being dispersed in the electrolyte membrane; The membrane electrode assembly according to claim 1 , further comprising:

7. The membrane electrode assembly according to claim 6 , wherein the second metal element is Ce.

8. The membrane / electrode assembly according to claim 6 or 7, which satisfies the following formula (1): 0.0005≦M / A≦0.15 (1) however, M / A is the ratio of the number of moles (M) of the second metal element to the number of moles (A) of the acid groups contained in the solid polymer electrolyte.

9. The membrane / electrode assembly according to claim 1 , wherein the first fine particles are unevenly distributed in an in-plane direction.

10. a first step of attaching first fine particles made of a first compound having a function of decomposing hydrogen peroxide to a surface of an electrolyte membrane and / or a surface of an anode catalyst layer facing the electrolyte membrane; a second step of forming the anode catalyst layer on the anode side surface of the electrolyte membrane such that the surface to which the first fine particles are attached faces inward, and further forming a cathode catalyst layer on the other side of the electrolyte membrane to form a laminate; A third step of heat-treating the laminate to obtain the membrane-electrode assembly according to any one of claims 1 to 9. The present invention relates to a method for producing a membrane electrode assembly.

Citation Information

Patent Citations

  • Solid polymer fuel cell

    JP2005267904A

  • Membrane electrode assembly using peroxide decomposition catalyst

    JP2005538508A

  • Polymer electrolyte fuel cell and its manufacturing method

    JP2006079904A

  • Encoder system

    JP2008098996A

  • CATALYST FOR RuTe2-CONTAINING DMFC TYPE FUEL CELL, ELECTRODE MATERIAL FOR FUEL CELL USING THE CATALYST FOR FUEL CELL, AND FUEL CELL

    JP2009252411A